The Roles, Challenges & Improvement of Project Manager in Project Financial Management in Building Development in Penang, Malaysia - Kiu Mee San; Salman Riazi Mehdi Riazi; Mohd Nasrun Mohd Nawi; Muneera Esa (International Journal of Supply Chain Management, 2017)
Project Manager holds roles and responsibilities to ensure the success of construction projects for his organisation. And one of the roles is to ensure the well-management of Project Financial Management in his organisation. Recent research has identified project cost overrun has been a major issue in construction industry. These project cost overrun cases have been repeating and have reduced the profit and revenues of the project owners. Therefore, it comes across the researchers mind of what the project managers who work for developer companies have been doing in order to overcome repeated cost overrun cases in the near future project developments. Hence, the set objectives of the research are: 1) To identify the important roles of Project Manager in Financial Management in building project development in Malaysia, 2) To identify challenges faced by Project Manager in Financial Management of building project development in Malaysia. 3) To identity solutions to overcome such challenges faced in Financial Management in building project development in Malaysia. However, due to time constraint, this research is limited and carried out in Penang, which is the second-smallest state in Malaysia, with strong population growth and has undertaken numerous construction projects in Malaysia. The research methodology used for this study is qualitative approach. Semi-structured interviews are used as research instrument for the data collection for this research. An overall of six interviews had been conducted with highly experienced Project Managers in Penang construction industry who has the knowledge and experiences in the Financial Management of building development. The data from the successful interviews are then been analysed using content analysis method in which the data collected are categorized into groups in table forms. From the findings, the respondents had defined the Project Financial Management relating to three main aspects. Four (4) out of six (6) respondents are having moderate involvement and two (2) respondents are having high involvement in the Financial Management in building development in Penang. The research findings had also identified five (5) major roles of project manager in Project Financial Management. Furthermore, five (5) major challenges of project manager in Project Financial Management were also identified. Finally, research findings also identified four (4) major solutions to overcome the challenges faced by project manager in Project Financial Management. Ultimately, this research is anticipated to create awareness of the important roles of Project Manager in Project Financial Management to mitigate the cost overrun issues in construction projects.